2019
DOI: 10.3390/su11205764
|View full text |Cite
|
Sign up to set email alerts
|

Fish is the Preferred Animal-Source Food in the Rural Community of Southern Bangladesh

Abstract: Increased intake of animal-source foods (ASFs) is crucial to tackle multiple nutritional challenges in Bangladesh, and contribute to achieving targets under the Sustainable Development Goals (SDGs). Qualitative and quantitative data were collected to assess current ASFs intake behaviors and preferred ASFs, among three types of households, namely 1. aquaculture intervention (AI); 2. aquaculture non-intervention (ANI); and 3. non-aquaculture non-intervention (NANI) households and children aged 6-59 months, to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(44 reference statements)
2
6
0
Order By: Relevance
“…More than four quintiles of the WRA had an inadequate dietary intake of folic acid, and nearly three quarters of them had an inadequate vitamin B12 intake in the preceding 24 h. These results are consistent with studies conducted in rural Bangladesh showing inadequate animal-source food intake as one of the contributing factors, particularly for lower dietary vitamin B12 intake [ 9 , 39 ], as animal foods are the only source of vitamin B12. Although fish is the most commonly consumed and preferred animal-source food in Bangladesh, the quantity of intake is minimal [ 9 , 39 ]. B vitamins play important roles in the normal functioning of our body; particularly, folic acid and vitamin B12 deficiencies are associated with adverse maternal and neonatal outcomes [ 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…More than four quintiles of the WRA had an inadequate dietary intake of folic acid, and nearly three quarters of them had an inadequate vitamin B12 intake in the preceding 24 h. These results are consistent with studies conducted in rural Bangladesh showing inadequate animal-source food intake as one of the contributing factors, particularly for lower dietary vitamin B12 intake [ 9 , 39 ], as animal foods are the only source of vitamin B12. Although fish is the most commonly consumed and preferred animal-source food in Bangladesh, the quantity of intake is minimal [ 9 , 39 ]. B vitamins play important roles in the normal functioning of our body; particularly, folic acid and vitamin B12 deficiencies are associated with adverse maternal and neonatal outcomes [ 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…Secondly, households that produced nutrient-rich foods were likely to consume these same foods. These findings are consistent with those from other studies that have demonstrated that people eat many of the foods they produce [ 40 , 41 , 42 , 43 , 44 ]. Dietary intakes largely depend on foods supplied from households’ own farms among smallholders, particularly if they are more distant from food markets [ 16 , 17 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…As reported by households with both forms of engagement, the source of nutrient-rich foods was mostly from households' own production. Fish is the most commonly consumed animal source food (ASF) in Bangladesh [43,54,55] compared to other ASFs such as chicken, milk, eggs, duck, and red meat. Studies have shown that adding a small amount of ASFs to a plant-based diet can enhance the absorption of vitamins and minerals from these foods, and can significantly impact maternal health and child development [1,10,13].…”
Section: Discussionmentioning
confidence: 99%
“…Economic access was examined in almost two thirds of included studies. Affordability relative to other animal-source foods and the opportunity for households to purchase small quantities of fresh fish or fish-based products according to their financial means are key advantages of fish, as has been highlighted elsewhere [ 65 , 66 , 67 ]. Despite this, diets containing optimal amounts of fish to meet nutrient requirements were shown to substantially increase the overall cost of diet in populations largely reliant on plant-source foods [ 41 ].…”
Section: Discussionmentioning
confidence: 99%